Thermal and thermodynamic comparison of smooth and convergent‐divergent parabolic trough absorber tubes with the application of mono and hybrid nanofluids. (3rd November 2020) - Khan, Muhammad S.; Abid, Muhammad; Yan, Mi; Ratlamwala, Tahir A. H.; Mubeen, Ishrat
Summary: The utilization of hybrid nanofluids is a promising technique in the high temperature solar applications specially, parabolic trough collector (PTC). The purpose of the current research is to analyze, evaluate and compare the performance of PTC (converging‐diverging absorber tube) using mono and hybrid nanofluids to increase the convective heat transfer coefficient. To obtain this objective, converging‐diverging tube with sine geometry is examined as it enhances the turbulence in the flow due to increase in the inner surface roughness. The performance of the absorber tube is assessed for hybrid nanofluid (1.5% MWCNTs/therminol‐VPI and 1.5% TiO2 /therminol‐VPI) as well as mono nanofluids (3% MWCNTs and 3% TiO2 )/therminol‐VPI at a wide range of inlet temperature ranges from 350 K to 600 K. In order to compare the results of the converging‐diverging tube, a smooth absorber tube is also investigated at the same design conditions. Furthermore, our study comprises of the overall performance investigation about the exergy analysis, pressure drop, pumping power required and performance evaluation criteria to investigate the comprehensive performance of the absorber tubes. The results of the study reveal that the use of modified geometry with hybrid nanofluids considerably improves the performance of the system due to the presence of swirls and turbulence that will reduce absorber surface temperature and ultimately the heat losses. More specifically, the thermal efficiency enhancement for the converging‐diverging absorber tube with hybrid nanofluids ranges from 3.61% to 5.27%, while it is varied from 1.70% to 1.91% for smooth tube using hybrid nanofluids. Reynolds number ranges from 12 000 to 90 300 for hybrid nanofluid, while it is from 14 000 to 97 600 for pure therminol‐VPI. Furthermore, mean enhancement in the heat transfer coefficient using converging‐diverging tube with hybrid, TiO2 and MWCNTs therminol‐VPI‐based nanofluids are 1.72%, 0.67% and 0.70%, respectively at a mass flow rate of 0.6 kg/s and an ambient temperature of 300 K. The converging‐diverging/hybrid case has the values of 1.47 and 1.33 for performance evaluation criteria I and II, while all other cases has significantly less values compared to hybrid nanofluids. The thermal efficiency enhancement has a pressure‐drop penalty that leads to higher pumping power requirement; however, this requirement is very small as compared to the useful energy gain.